-3+3x=-2(x+1)
First: I will get rid of the bracket:
-3+3x=-2x-2
Now, all the x goes to the left side, all the numbers without x to the right side:
3x+2x=-2+3
we add up"
5x=1
divide by 5:
Answer:
3
Step-by-step explanation:
see image
Answer:
Simplifying 6x * 3y * 9x2y4 Reorder the terms for easier multiplication: 6 * 3 * 9x * y * x2y4 ... When you enter an expression into the calculator, the calculator will simplify the ... For addition and subtraction, use the standard + and - symbols respectively.
Step-by-step explanation:
Options 1 and 3 are the correct answers